Penegakan Hukum Terhadap Peredaran Narkotika Jenis Ganja berdasarkan Undang-Undang Nomor 35 Tahun 2009 tentang Narkotika di Wilayah Hukum Kepolisian Resor 50 Kota Sumatera Barat - Intan Purnama Sari; Syaifullah Yophi A; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Narcotic crime always increasing number of cases, suspect, and victim every years. Abuse problem and ilicit traffic in narcotic drugs have shown poor condition and a threat to the survival of the nation especially district of 50 Kota Sumatera Barat. Based of data obtained by author from Polres 50 Kota Sumatera Barat, law enforcement against narcotics type of marijuana have been implemented but still not optimally. There are still many obstacles and barriers perceived by members of the narcotics detectives that cause less maximal law enforcement in this area. Some of the barriers and constraints experienced in law enforcement against drug trafficking, among others, the limited number of police personnel in handling narcotic cases, limited operational funds, limited skills or abilities of the personnel, and several other constraints. That's a few things cause more illicit trafficking of narcotics, especially type of marijuana in the district 50 Kota Sumatera Barat.Based on the authors formulate three problems, namely, first, how law enforcement against illicit traffic in narcotic type of marijuana based on the Narcotics law in Polres 50 Kota Sumatera Barat, the second what are the constraints faced by the polres 50 kota sumatera barat in law enforcement against illicit traffic in narcotic type of marijuana based on the Narcotics law,the third what are the three attempts made Polres 50 Kota Sumatera Barat to overcome obstacles in law enforcement against illicit traffic in narcotic type of marijuana based on the Narcotics law in Polres 50 Kota Sumatera Barat.This type of research if the views of its kind, this research can be classified to sociological research. Sociological research is the study of law directly into the field to find the data in the institutions related to the research conducted. Source of data used are primary data and secondary data, data collection techniques in this study with the literature study and interviews.From this research we can conclude the authors first, law enforcement against illicit traffic in narcotic type of marijuana based on the Narcotics law in Polres 50 Kota Sumatera Barat was carried out to the fullest. Even so, in enforcing the law there are still some obstacles faced by police officers, The constraints faced by the Polres 50 Kota Sumatera Barat in enforcing the law against narcotic type of marijuana have two (2) factors: internal factors and external factors third, the efforts made by the Polres 50 Kota Sumatera Barat in overcoming these obstacles is to fix the flaws in the internal and external police.Keywords : Law Enforcement – Narcotic Crime